Rapidly increasing trend of recorded alcohol consumption since the end of the armed conflict in Sri Lanka - Nugawela, Manjula D.; Lewis, Sarah; Szatkowski, Lisa; Langley, Tessa (Oxford University Press, 2017)
Aim: To evaluate temporal changes in recorded alcohol consumption in Sri Lanka during and after the armed conflict 1998 – 2013.